The effect of moderate exercise on serum immunoglobulin levels among secondary schoolchildren - Mohamad Fauzi, Nor Farah (2001)
Recent studies have reported that enhancement in immunity occur following a moderate exercise bout, acommpanied by an increase in neutrophils, lymphocytes, augmented NK cells activity, and an increase in serum immunoglobulins levels. However, limited empirical evidence exists on the influence of moderate exercise training on humoral immunity, particularly among the youth. Therefore, the aim of the present study was to investigate the relationship between moderate exercise training and changes in serum immunoglobulin levels in adolescents. Thirty-five (n=35), physically inactive male residential school-going students aged 16 years, matched for BMI and fitness level were recruited and subjected to three 45-minute jogging sessions per week at 60% to 75% of heart rate reserve. A lO-ml blood sample was collected from each subject prior to and after the implementation of exercise programme for the determination of serum immunoglobulins using single radial immunodiffusion technique. Results were analyzed using Student's paired-t test. Serum IgG and IgM levels were found to be significantly (p<0.001) increased (13.79 ± 0.27 gil and 1.34 ± 0.02 gil respectively) after eight weeks of exercise training relatively to baseline values. A significant (p<O.05) increases in erythrocyte, hemoglobin, and haematocrit levels were also observed. No differences were observed in IgA levels, leukocyte, and platelet counts. The eight weeks of moderate exercise training also resulted in a significant (p<O.OO I) decrease in resting heart rate and improved I-Mile run performance. This study indicates that eight weeks of moderate exercise training produced significant increases in serum IgG and IgM levels as well as other hematological parameters in previously physically inactive adolescents.